MMS Observations and Hybrid Simulations of Surface Ripples at a Marginally Quasi‐Parallel Shock. Issue 11 (3rd November 2017) - Gingell, Imogen; Schwartz, Steven J.; Burgess, David; Johlander, Andreas; Russell, Christopher T.; Burch, James L.; Ergun, Robert E.; Fuselier, Stephen; Gershman, Daniel J.; Giles, Barbara L.; Goodrich, Katherine A.; Khotyaintsev, Yuri V.; et al.
Abstract: Simulations and observations of collisionless shocks have shown that deviations of the nominal local shock normal orientation, that is, surface waves or ripples, are expected to propagate in the ramp and overshoot of quasi‐perpendicular shocks. Here we identify signatures of a surface ripple propagating during a crossing of Earth's marginally quasi‐parallel ( θ B n ∼45 ∘ ) or quasi‐parallel bow shock on 27 November 2015 06:01:44 UTC by the Magnetospheric Multiscale (MMS) mission and determine the ripple's properties using multispacecraft methods. Using two‐dimensional hybrid simulations, we confirm that surface ripples are a feature of marginally quasi‐parallel and quasi‐parallel shocks under the observed solar wind conditions. In addition, since these marginally quasi‐parallel and quasi‐parallel shocks are expected to undergo a cyclic reformation of the shock front, we discuss the impact of multiple sources of nonstationarity on shock structure. Importantly, ripples are shown to be transient phenomena, developing faster than an ion gyroperiod and only during the period of the reformation cycle when a newly developed shock ramp is unaffected by turbulence in the foot. We conclude that the change in properties of the ripple observed by MMS is consistent with the reformation of the shock front over a time scale of an ion gyroperiod. Key Points: A surface ripple has been observed by MMS at Earth's quasi‐parallel bow shock Hybrid simulations show that these ripples are transients modulated by shock reformation Changes in the observed ripple are consistent with reformation processes